Identification of bottlenecks in the accumulation of cyclic fatty acids in camelina seed oil. Issue 4 (18th January 2018) - Yu, Xiao‐Hong; Cahoon, Rebecca E.; Horn, Patrick J.; Shi, Hai; Prakash, Richa R.; Cai, Yuanheng; Hearney, Maegan; Chapman, Kent D.; Cahoon, Edgar B.; Schwender, Jorg; Shanklin, John
Summary: Modified fatty acids (mFA) have diverse uses; for example, cyclopropane fatty acids (CPA) are feedstocks for producing coatings, lubricants, plastics and cosmetics. The expression of mFA‐producing enzymes in crop and model plants generally results in lower levels of mFA accumulation than in their natural‐occurring source plants. Thus, to further our understanding of metabolic bottlenecks that limit mFA accumulation, we generated transgenic Camelina sativa lines co‐expressing Escherichia coli cyclopropane synthase (EcCPS) and Sterculia foetida lysophosphatidic acid acyltransferase (SfLPAT). In contrast to transgenic CPA‐accumulating Arabidopsis, CPA accumulation in camelina caused only minor changes in seed weight, germination rate, oil accumulation and seedling development. CPA accumulated to much higher levels in membrane than storage lipids, comprising more than 60% of total fatty acid in both phosphatidylcholine (PC) and phosphatidylethanolamine (PE) versus 26% in diacylglycerol (DAG) and 12% in triacylglycerol (TAG) indicating bottlenecks in the transfer of CPA from PC to DAG and from DAG to TAG. Upon co‐expression of SfLPAT with EcCPS, di‐CPA‐PC increased by 50% relative to lines expressing EcCPS alone with the di‐CPA‐PC primarily observed in the embryonic axis and mono‐CPA‐PC primarily in cotyledon tissue. EcCPS‐SfLPAT lines revealed a redistribution of CPA from the sn ‐1 to sn ‐2 positions within PC and PE that was associated with a doubling of CPA accumulation in both DAG and TAG. The identification of metabolic bottlenecks in acyl transfer between site of synthesis (phospholipids) and deposition in storage oils (TAGs) lays the foundation for the optimizing CPA accumulation through directed engineering of oil synthesis in target crops.